Deconvolution of Leukemic Evolution Through Initiation, Progression and Relapse - Dobson, Stephanie M (ProQuest Dissertations & Theses, 2017)
Significant advancements in the study of the genomic architecture of B-cell acute lymphoblastic leukemia (B-ALL) have been made, but our understanding of the mechanisms of leukemic initiation and progression remain limited. To gain clarity on these processes, a deeper understanding of the co-operative role of genetic aberrations, the functional impact of clonal diversity and the cellular target of transformation are required. Human models of leukemogenesis are vital in answering these questions. Using primary human umbilical cord blood cells, transduced with leukemic variants in a xenograft assay, we uncovered the importance of novel transcriptional programs, including induced stem cell transcriptional programs, in leukemogenic transformation. Recent evidence has shown that in the majority of B-ALL patients, relapse arises from a minor ancestral clone present in the diagnosis sample. An important question therefore arises as to what functional properties these clones possess and whether therapy resistance is acquired following treatment or is an intrinsic property of pre-existing cells. Using paired diagnosis and relapse patient samples in combined genomic and functional assays, we determine that minor ancestral clones present at diagnosis display decreased therapeutic response and are thus fated to relapse. These findings emphasize the need for improved minimal residual disease monitoring (MRD) and the development of therapeutic strategies that eliminate all genetic clones equally to prevent disease recurrence. Chromosomal translocations in B-ALL are known to be early initiating events occurring prenatally in some pediatric B-ALL patients, but there is conflicting data on their cellular origin. Using paired umbilical cord blood and leukemic samples, we found evidence that bi-lineage progenitors may act as the reservoir of pre-leukemia in pediatric B-ALL. Collectively, our work sheds light on the origin of disease and disease recurrence in B-ALL. By deepening the understanding of the forces at play leading to selection and expansion during disease evolution, novel therapeutic strategies can be developed to improve patient outcomes.